Impact of financial structure (Banks & Markets based) and economic growth: An Econometric Study for a sample of 85 countries over the Period (1990-2020) - بيري , نورة; دبوش , عبد القادر (Finance and Business Economies Review, 2023)
Various arguments have been advanced by policymakers and economists concerning the relevance of bank-based and market-based structure in explaining the economic growth. The aim of this study is examine the finance-growth nexus, based on structure categories. To estimate the impact of financial structure (bank-based and market-based) on economic growth in 85 countries during the period from 1990 to 2020, the paper uses a Cross-country data. The results of the study confirm that there is no effect for the bank-based or market-based views financial structure on economic growth. Rather the study opined that it is the provision of financial services (combination of banks and financial markets) has a positive impact on the economic growth.